ANDESAURUS DELGADOI GEN ET SP. NOV. (SAURISCHIA-SAUROPODA), DINOSAURIO TITANOSAURIDAE DE LA FORMACION RIO LIMAY (ALBIANO-CENOMANIANO), NEUQUEN, ARGENTINA (Ameghiniana, 2013)
A good part of the postcranial skeleton of an Albian-Cenomanian primitive titanosaurid from Patagonia is described and discussed. The posterior dorsal vertebrae are high, with slight opisthocoelious centrum, a tall neural spine and hyposphene-hypanthrum articulations, The medial and distal caudal vertebrae are amphylatian, bearing flat, quadrangular neural spines. Ischium and pubis show clear titanosaurid features. Some characters of the dorsal vertebrae and pubis resemble those of Argyrosaurus superbus? but is not possible to recognize any direct relationship. The relative prirnitive condition of this new titanosaurid permitted to propose a new subfamily for it, Andesaurinae nov., representing a stage of evolution less derived than that of typical Senonian titanosaurids. It is argued that the latter were endemic and very diversified, representing the major herbivorous group of the Late Cretaceous fauna of Gondwana.